Sialic Acids in the Immune Response during Sepsis - Liu, Yan-Cun; Yu, Mu-Ming; Chai, Yan-Fen; Shou, Song-Tao (Frontiers in Immunology, 2017)
Siglecs are a group of cell surface transmembrane receptors expressed on immune cells, and regulate immune balance in inflammatory diseases. Sepsis is a life threatened inflammatory syndrome induced by infection, and the pathogenesis of sepsis includes immune dysregulation, inflammation, and coagulation disorder. Here we reviewed the various roles acted by Siglecs family in the pathogenesis of sepsis. Siglec-1, siglec-5 and siglec-14 plays bidirectional roles through modulation of inflammation and immunity. Siglec-2 regulates the immune balance during infection by modulating B cell and T cell response. Siglec-9 helps endocytosis of Toll like receptor 4, regulates macrophages polarization, and inhibits the function of neutrophils during infection. Siglec-10 inhibits danger associated molecular patterns induced inflammation, helps the initiation of antigen response by T cells, and decreases B-1a cell population to weaken inflammation. Regulating the Siglecs function in the different stages of sepsis holds great potential in the therapy of sepsis.